Financiamento da educação básica no Brasil: uma análise das propostas para a complementação da União na definição do novo FUNDEB - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Fundeb is an important mechanism to finance basic education, created in 2006, with a term of validity until December 30, 2020. With a period of validity, since 2015 the substitute for this mechanism has been discussed. There was movement of several segments of society so that the fund for education was permanent and with greater contribution of the Union. This study analyzes the percentage proposals for the complementation of the Union in the new Fundeb, presented at the public hearings promoted by the Special Committee to deliver an opinion on the Proposed Amendment to the Constitution of the Novo Fundeb. The methodological procedures performed were: bibliographic and documentary research. We opted for a qualitative approach, using the documental analysis of PEC No. 15/2015, public hearings and shorthand notes of that PEC, in the period from 2017 to 2019. The analysis of the documents showed that the proposals relating to the complementation of the Union were the subject of the greatest clashes. In these clashes, two fronts were identified: those that defend the efficiency of public spending and those who fight for the resources necessary to guarantee the law and public education.
Keywords: Financiamento; Eficiência dos gastos públicos; Educação básica pública; Políticas públicas educacionais; Qualidade do ensino; CIÊNCIAS HUMANAS; Novo Fundeb; Complementação da União; Educação básica